Belimumab in childhood systemic lupus erythematosus: A review of available data - Chen, Feng; Zheng, Ying; Chen, Xinying; Wen, Zhanfa; Xu, Youjia; Yang, Jinghua; Xu, Kaisi (Frontiers in Immunology, 2022)
Abstract Introduction: Childhood systemic lupus erythematosus (cSLE) is a complex multisystem autoimmune disease. In 2019, belimumab was approved for the clinical treatment for cSLE, making it the only biological agent approved for cSLE children aged 5 and older in 60 years. Objective: To review emerging evidence on belimumab in cSLE published up to April 2022, so as to provide information for clinical decision-making. Method: A comprehensive search of relevant publications up to the date of April 2022 in PUBMED, EMBASE, WOS, COCHRANE, ClinicalTrials.gov, CBM, CNKI and WANFANG was performed using the following criteria: (a) English and Chinese language studies; (b) RCT studies, cohort studies, or case-control studies; (c) patients with age <18; (d) Observational studies or case series studies contain more than 5 patients. All relevant literature was independently screened and reviewed by at least two reviewers and the obtained literature data were extracted and reviewed by two authors. Results: Five publications met the inclusion/exclusion criteria for cSLE: one randomized controlled trial, one retrospective cohort study, and three case series. There was a high degree of heterogeneity among several studies, and the availability of baseline and outcome data provided was uneven. Conclusion: At present, there is a lack of high-quality clinical trials of belimumab in the treatment of cSLE. Based on the current research, it is believed that the use of belimumab can inhibit cSLE activity, reduce the dose of corticosteroids and immunosuppressants, and delay kidney damage. Also it shows clinical benefit in alleviating symptoms of monogenic cSLE refractory to standard therapy. More studies are urgently needed to validate the clinical efficacy of belimumab in cSLE and to evaluate its long-term safety in pediatric populations to promote evidence-based practice.